Anna's birthday surprise - Julius, Jessica (New York : Random House, 2015)
Elsa and Kristoff's efforts to organize a birthday party for Anna are complicated by an unexpected chill that falls over the festivities.
At head of title: Disney Frozen fever.
Keywords: Birthday parties -- Fiction; Princesses -- Fiction; Sisters -- Fiction; Birthday parties -- Fiction; Princesses -- Fiction; Sisters -- Fiction; Movie novels